Penerapan Metode System Usability Scale (SUS) Pada Analisis Usability Aplikasi Gramedia Mobile - Mahmud Safudin; Fada Nazarulloh Muttin; Setiaji Setiaji (Universitas Bina Sarana Informatika, 2026)
The rapid development of digital technology has significantly influenced public behavior, particularly in reading and purchasing books online. PT Gramedia Asri Media responded to this trend by launching the Gramedia Mobile application to provide users with an easier way to browse and purchase books. However, user reviews on the Google Play Store indicate that the application's usability still requires evaluation. This study aims to analyze the usability level of the Gramedia Mobile application using the System Usability Scale (SUS) method to obtain a quantitative overview of user perceptions regarding ease of use, efficiency, and satisfaction. The research employed a quantitative approach through a SUS questionnaire distributed to 100 Gramedia Mobile users. Data were analyzed using the official SUS scoring formula and validated through reliability and validity testing. The results show that the Gramedia Mobile application achieved an average SUS score of 79.78, categorized as grade A− within the 85–89 percentile range. This indicates that the application has good usability and is generally acceptable to users. The strongest usability dimension is learnability, where users find the application easy to learn and operate. Overall, the application is considered feasible but still has room for improvement to achieve the “Excellent” usability category.